The Influence of Social Media on Language Creativity among Students: An Empirical and Theoretical Perspective - Hasanah, Uswatun; Firdaus, Rangga; Hariri, Hasan; Handoko; Siregar, Rabiyatul Adawiyah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
The proliferation of social media as a dominant mode of digital communication has engendered profound transformations in language practices within higher education, particularly at Islamic institutions where academic discourse intersects with religious communication ethics. This study investigates the influence of social media language creativity—encompassing slang, abbreviations, code-mixing, and neologisms—on the linguistic proficiency of students at the Faculty of Sharia, Universitas Islam Negeri (UIN) Raden Intan Lampung. Employing a qualitative descriptive approach integrated with a systematic literature review, primary data were collected through participatory observation and semi-structured interviews with 60 students drawn from three study programs (Islamic Family Law, Sharia Economic Law, and Constitutional Law) via purposive sampling. Secondary data were obtained from peer-reviewed publications spanning 2020–2025. Findings reveal a dual impact of social media language use: on the one hand, digital platforms foster vocabulary enrichment, linguistic creativity, and innovative communicative strategies—including the adaptation of informal registers for digital da'wah; on the other hand, habitual exposure to informal digital language diminishes the consistency of standard Indonesian in academic contexts, manifesting as grammatical imprecision, register conflation, and reduced formal writing quality. Content analysis further identifies five principal factors driving slang adoption: the need to follow digital trends (93%), peer group influence (90%), social media as a vocabulary source (87%), communication efficiency (80%), and linguistic creativity (72%). Notably, students demonstrate context-dependent register switching, predominantly employing informal registers in peer communication (92%) while reverting to standard Indonesian in academic presentations (90%). These findings underscore the necessity of strengthening digital literacy programs, institutional language policies, and pedagogical interventions that balance creative expression with formal academic standards in Islamic higher education.